PENERAPAN SUB POKOK FUNGSI LINEAR TERHADAP ANALISIS BREAK EVEN POINT (ANALISIS IMPAS) PADA PERENCANAA LABA PT. KORMA JAYA UTAMA - Bagas Astaghinanim; M Alpiah Rocah; Muhammad Rizky Fadillah (Taksasila Edukasi Insani, 2026)
This study focuses on examining the application of linear sub-functions in Break-Even Point (BEP) analysis for profit planning at PT. Korma Jaya Utama. The method used is descriptive quantitative analysis with a case study approach. The data evaluated includes the company's consolidated financial statements for 2024, which consist of information on sales, fixed costs, variable costs, and sales volume. Data analysis was performed using a cost-volume-profit (CVP) approach that integrates a linear function model to calculate BEP in units and rupiah value, safety margin, and profit target planning. The research findings show that PT. Korma Jaya Utama's BEP is recorded at a sales level of 8,568 bottles or equivalent to IDR 256,686,025. The safety margin of 92.9% indicates that the company's financial position is quite stable. Additionally, to achieve the profit target of IDR 60,165,360, the company must achieve sales of IDR 473,108,183. These results indicate that the application of linear functions in BEP analysis is an effective tool for profit planning and managerial decision-making.Keywords: Linear Function, Break-Even Point, and Profit Planning